(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The COVID-19 pandemic created a global health crisis unlike any other in recent memory. Organizations’ hiring practices are already changing to reflect the new reality of a post-COVID-19 society. Also, to avoid close contact with people, businesses became much more reliant on remote meeting software for various employment purposes than they were previously. This research assessed the validity of a proposed flexible hiring process policy for higher education institutions. Questions were formulated to guide the study. The population of the study consists of HR Personnel. Through the purposive sampling method, fifteen (15) respondents were selected to participate in the study. The major instrument used for gathering data was a survey questionnaire. The data gathered were analyzed using percentages, weighted mean, and chi-square to determine the hypothesis of this study. Most HR Personnel are female, 25-30 years old, a bachelor’s degree graduate, and 1-5 years of academic experience. On assessing the validity of the proposed flexible hiring process policy in terms of the policy title, purpose, scope, policy statement, guidelines, procedure, definition, frequently asked questions, contact, references, and approval, have a verbal interpretation of “very valid.” The degree of recommendation by the HR Personnel in the proposed flexible hiring process policy was highly recommended. The assessment of the validity of the proposed flexible hiring process policy and its indicators has a Very Valid (VV) verbal interpretation. Furthermore, there is no significant difference in the validity of the proposed flexible hiring process policy when the profile is considered. Based on the study findings, HR personnel highly recommend the Proposed Flexible Hiring Process Policy.